Answer: The answer is f(x) = (x-3)²-h = (x-3-√h)(x-3+√h).
Step-by-step explanation: We are given to write a quadratic function in factored form that would have a vertex with an x-coordinate of 3 and two distinct roots.
A quadratic function with vertex having x-coordinate k takes the form of a parabola as follows:
![f(x)+h=(x-k)^2.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/uy8owwsdb3q5vq8shfx1vivr1loqf702w6.png)
Here, 'k' and 'h' are both real.
Since we the the x-coordinate of the vertex as 3, so k = 3.
Therefore, the quadratic function becomes
![f(x)+h=(x-k)^2\\\\\Rightarrow f(x)=(x-k)^2-h\\\\\Rightarrow f(x)=(x-3-\sqrt h)(x-3+\sqrt h).](https://img.qammunity.org/2020/formulas/mathematics/middle-school/geyqq9geve3ubnio3qoqqd13vp21ubvyxb.png)
This is the required factored form of the quadratic function.
See the attached graph, where the x-coordinate of the vertex is 3 and h is taken to be 2 units.